Permodelan hidrogeologi kondisi natural pada daerah luyo kabupaten polewali mandar provinsi sulawesi barat - Nur Aqsa Syahban Irwan; Shalaho Dina Devy; Albertus Juvensius Pontus; Revia Oktaviani; Agus Winarno (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The Luyo area, Polewali Mandar Regency, West Sulawesi Province, has a high dependence on groundwater as the main source of water for domestic and community activities. Increasing groundwater utilization may potentially disturb the natural hydrogeological balance if it is not properly managed. Therefore, a comprehensive understanding of natural hydrogeological conditions is essential as a basis for sustainable groundwater management. This study aims to determine the hydrogeological conditions of the study area, the natural groundwater balance, and the groundwater flow pattern and hydraulic head distribution through natural-condition hydrogeological modeling. The research methods include hydrological analysis, groundwater level measurements, electrical resistivity surveys using the Schlumberger configuration, pumping tests, and steady-state numerical groundwater modeling based on conceptual and mathematical approaches. The results indicate that the hydrogeological system in the study area consists of unconfined and semi-confined aquifers controlled by local lithological and geomorphological conditions. The natural groundwater balance shows that the study area remains in a relatively balanced condition, with groundwater recharge primarily derived from rainfall infiltration. Groundwater flow generally follows the topography, moving from recharge areas toward discharge zones such as rivers and springs. Model calibration results show good agreement between simulated and observed hydraulic heads. The developed natural-condition hydrogeological model is expected to serve as a baseline reference for evaluating future changes in the groundwater system due to human activities and environmental changes